EPISTEMOLOGI POLITIK DI BANGKU SD: DUALISME PERAN GURU SEBAGAI AGEN KEBENARAN DAN KEKUASAAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Political education at the elementary school level plays a strategic role in shaping children's understanding of the state, power, and democratic life. However, political learning in elementary schools is still dominated by normative and rote learning approaches, especially regarding state symbols, government structures, and moral rules, leaving no room for the development of critical thinking skills. This article examines how political epistemology is constructed through the curriculum, textbooks, and pedagogical practices, as well as how teachers play a dual role as agents of truth and agents of power. This study uses a Systematic Literature Review (SLR) approach to thirty articles published between 2020 and 2025 to map epistemological patterns, knowledge-power relations, and opportunities for developing critical political literacy in elementary school students. The results show that the construction of political knowledge in elementary schools is still one-way, declarative, and non-dialogical, influenced by hierarchical school structures and learning practices that prioritize obedience. Textbooks reinforce simplistic and idealistic political narratives. However, various studies reveal that students have the epistemic potential to understand political issues reflectively if learning provides space for dialogue, contextual experiences, and participatory approaches. This study emphasizes that reconstructing political epistemology through curriculum reform, capacity building, and participatory approaches are important steps in developing critical political literacy among elementary school students.